Cyberpunters and cyberwhores: prostitution on the internet - Earle, Sarah (2003)
About the book: Cyberspace opens up infinitely new possibilities to the deviant imagination. With access to the Internet and sufficient know-how you can, if you are so inclined, buy a bride, cruise gay bars, go on a global shopping spree with someone else's credit card, break into a bank's security system, plan a demonstration in another country and hack into the Pentagon -- all on the same day. In more than any other medium, time and place are transcended, undermining the traditional relationship between physical context and social situation. This book crosses the boundaries of sociological, criminological and cultural discourse in order to explore the implications of these massive transformations in information and communication technologies for the growth of criminal and deviant identities and behaviour on the Internet. This is a book not about computers, nor about legal controversies over the regulation of cyberspace, but about people and the new patterns of human identity, behaviour and association that are emerging as a result of the communications revolution